The Savvy Survey #9: Gaining Institutional Review Board Approval for Surveys - Colleen E. Gariton; Glenn D. Israel (EDIS)
Getting IRB approval for your survey can seem like a daunting task to many people in academia and Extension. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication discusses what the IRB is, when and how to get IRB approval for a survey, getting informed consent, and where to get help for Extension professionals wanting to perform research or publish findings from surveys they have completed. Written by Colleen E. Gariton and Glenn D. Israel.